Additional radiation dose due to atmospheric dispersion of tritium evaporated from a hypothetical reservoir. (January 2021) - Nie, Baojie; Yang, Jinmin; Yuan, Yuan; Li, Fengchen
Abstract: With regard to an inland nuclear power plant bordered by a reservoir, a major concern was that fresh water might be polluted and the human body might be radiation exposed due to the discharge of liquid radioactive effluents. In contrast to other radionuclides in the effluents, tritium has specific dispersion behavior in the aquatic environment such as emission into the air along with water evaporation. Further, the evaporated tritium in the air could go toward the territorial system where the wind blows. As a result, the person staying in the vicinity of the plant discharge point would be exposed with an additional radiation dose. In light of this characteristic, this study first introduced this new exposure pathway and investigated the additional radiation dose on the basis of a hypothetical reservoir. The results indicated that annual tritium evaporation fraction is approximately 2.5%, which is a comparable level with the radioactive decay factor. This would produce an additional radiation dose of 0.63 μSv/a to a person staying 50 m away from the plant discharge point for the case of 1 g/a tritium discharge. Tritium evaporation effects could be decreased through controlling the discharge depth. Thus, a preliminary suggestion to adopt a deep discharge instead of surface discharge was proposed from the ALARA (as low as reasonably achievable) criterion of radiation protection. Highlights: A new radiation exposure pathway associated to liquid tritium discharge was detailed. Tritium evaporation rate was estimated under various discharge conditions. Additional radiation dose was assessed due to tritium evaporation factor. A deep discharge instead of surface discharge was suggested from ALARA criterion.